Management of sinistra condyle fracture in emergency: case report - Cahyadi Siauw; Asri Arumsari; Endang Syamsudin; Fathurachman Fathurachman (DiscoverSys Inc., 2018)
Objective: Condyle fracture is a fracture that involves temporomandibular joint, resulting temporomandibular joint disorder. It often caused complications namely ankylosis and temporomandibular joint disorder. Trauma induced mandible fracture can leads to unilateral or bilateral condyle fracture.Method: Nine teen years old male came with mouth bleeding and pain on left lower jaw joint. Clinical examination showed laceration on right chin and left condyle fracture.Result: Management of patient to stitch laceration wound on chin region. Condyle fracture was treated conservatively using closed reduction method by arch bar and MMF rubber.Conclusion: Condyle fracture management needs a particular concern using closed method or conservative and open method or surgery. This present case chose closed method referring minimal displacement of condyle fracture.